ACTIONS THAT CONTRIBUTE TO SCIENCE TEACHING INVOLVING ARGUMENTATION AND THEIR RELATIONSHIPS WITH PEDAGOGICAL CONTENT KNOWLEDGE - Ibraim, Stefannie de Sá; Justi, Rosária (Investigações em Ensino de Ciências, 2022)
In argumentation-based science teaching, teachers play an important role and are the main party responsible for the introduction of argumentation in classrooms. In this study, we discuss how actions that contribute to science teaching involving argumentation are expressed by a teacher on leading different types of didactic sequences, and how such actions relate to teachers’ knowledge with regard to argumentation and teachers’ pedagogical content knowledge (PCK). For this reason, we have constructed an instrumental case study, based on the observation of four didactic sequences led by an experienced teacher, and through interviews with her. From their analysis, we conclude that the goals set by the teacher in the didactic sequences have had an influence upon the actions that contribute to science teaching involving argumentation shown by the teacher, suggesting a strong link between the elements of PCK and those of the Knowledge for Teachers’ Actions through Argumentation. As possible consequences, we draw attention to the need to add value to a hybrid method for teaching argumentation, involving implicit and explicit teaching, as well as the proposal of the set of actions that contribute to science teaching involving argumentation. This can contribute towards the investigations into the role of teachers within argumentation-based science teaching, and to teacher education.